Political Islam and Religiously Motivated Political Extremism: An International Comparison - Tausch, Arno (SpringerBriefs in Political Science, 2023)
This open access book presents an international comparison of religiously motivated extremism in the Arab world and around the globe. Based on data from the Arab Barometer and the World Values Survey, it applies advanced statistical techniques to analyze how religiously motivated political extremism affects political and social outcomes as well as political violence. The study clearly shows that identification with a political Islam that also influences elections, promotes religious and gender discrimination, and advocates an Islamist interpretation of Islam, are the main interrelated syndromes of political Islam that together explain more than 50% of the total variance of the 24 model variables used. “A carefully and methodically flawlessly researched work, which is highly recommended for all those who deal seriously with this topic. Professor Arno Tausch is clear-headed and possesses a remarkable ability to make the broad picture of Political Islam accessible.“ Hon. Prof. Gunther Hauser, Head of the Department Strategy and Security Policy, National Defense Academy, Vienna, Austria “Methodological rigorous, scientifically sound, empirically rich and combining the best of qualitative and quantitative approaches, Prof Arno Tausch has produced a tour de force on Political Islam. This study reflects the best scholarship on the subject and will be of use to both policy makers and academics.” Prof Hussein Solomon, Academic Head of the Department of Political Studies and Governance, University of the Free State, South Africa